Crotoxin Isolated from Crotalus durissus terrificus Venom Modulates the Functional Activity of Dendritic Cells via Formyl Peptide Receptors - A. P. Freitas; B. C. Favoretto; P. B. Clissa; S. C. Sampaio; E. L. Faquim-Mauro (Journal of Immunology Research)
The Crotalus durissus terrificus rattlesnake venom, its main toxin, crotoxin (CTX), and its crotapotin (CA) and phospholipase A2 (CB) subunits modulate the immune system. Formyl peptide receptors (FPRs) and lipoxin A4 (LXA4) are involved in CTX’s effect on macrophages and neutrophils. Dendritic cells (DCs) are plasticity cells involved in the induction of adaptive immunity and tolerance maintenance. Therefore, we evaluated the effect of CTX, CA or CB on the maturation of DCs derived from murine bone marrow (BM). According to data, CTX and CB—but not CA—induced an increase of MHC-II, but not costimulatory molecules on DCs. Furthermore, CTX and CB inhibited the expression of costimulatory and MHC-II molecules, secretion of proinflammatory cytokines and NF-κBp65 and p38/ERK1/2-MAPK signaling pathways by LPS-incubated DCs. Differently, CTX and CB induced IL-10, PGE2 and LXA4 secretion in LPS-incubated DCs. Lower proliferation and IL-2 secretion were verified in coculture of CD3+ cells and DCs incubated with LPS plus CTX or CB compared with LPS-incubated DCs. The effect of CTX and CB on DCs was abolished in cultures incubated with a FPRs antagonist. Hence, CTX and CB exert a modulation on functional activity of DCs; we also checked the involvement the FPR family on cell activities.